FIFO rosters and workers' health and safety: a case study of the impacts of extended shift rosters on electrical workers in construction in the resources sector. (1st October 2020) - Martin, John
ABSTRACT: Fly-in Fly-out (FIFO) employment has become a fundamental feature of construction activity in the resources sector in Australia. Much of the existing FIFO research has focused on the production phase of resource projects, as opposed to the construction phase. The rosters in the construction phase are less sociable than those in the production phase. Production phase-focused FIFO studies have documented negative impacts on communities, work-life balance and on the mental and occupational health of workers. This paper presents findings from a qualitative study among electrical trades workers working a challenging FIFO roster while employed during the construction phase of the INPEX LNG Project in Darwin in Australia's Northern Territory. Results from 18 semi-structured interviews are used to examine these rosters from the perspective of workplace health and safety. Findings are linked to obligations placed on the Person Conducting the Business or Undertaking (PCBU) by work health and safety legislation. The paper concludes that it is doubtful that these workers' rosters complied with the obligations placed on the PCBU by the legislation.